Retinal Organoids derived from hiPSCs of an AIPL1-LCA Patient Maintain Cytoarchitecture despite Reduced levels of Mutant AIPL1 - Lukovic, Dunja (Sci Rep, 2020)
Aryl hydrocarbon receptor-interacting protein-like 1 (AIPL1) is a photoreceptor-specific chaperone that stabilizes the effector enzyme of phototransduction, cGMP phosphodiesterase 6 (PDE6). Mutations in the AIPL1 gene cause a severe inherited retinal dystrophy, Leber congenital amaurosis type 4 (LCA4), that manifests as the loss of vision during the first year of life. In this study, we generated three-dimensional (3D) retinal organoids (ROs) from human induced pluripotent stem cells (hiPSCs) derived from an LCA4 patient carrying a Cys89Arg mutation in AIPL1. This study aimed to (i) explore whether the patient hiPSC-derived ROs recapitulate LCA4 disease phenotype, and (ii) generate a clinically relevant resource to investigate the molecular mechanism of disease and safely test novel therapies for LCA4 in vitro. We demonstrate reduced levels of the mutant AIPL1 and PDE6 proteins in patient organoids, corroborating the findings in animal models; however, patient-derived organoids maintained retinal cell cytoarchitecture despite significantly reduced levels of AIPL1.